Implementation of a Family Intervention for Individuals with Schizophrenia - Cohen, Amy N. (Springer-Verlag, 2010)
BACKGROUND: Families are rarely included in clinical care despite research showing that family involvement has a positive effect on individuals with schizophrenia by reducing relapse, improving work functioning, and social adjustment. OBJECTIVES: The VA QUERI study, EQUIP (Enhancing QUality of care In Psychosis), implemented family services for this population. DESIGN: At two VA medical centers, veterans with schizophrenia and their clinicians were interviewed separately at baseline and 15 months. A family intervention was implemented, and a process evaluation of the implementation was conducted. PARTICIPANTS: Veterans with schizophrenia (n = 173) and their clinicians (n = 29). INTERVENTION: Consent to contact family was obtained, mailers to engage families were sent, families were prioritized as high need for family services, and staff volunteers were trained in a brief three-session family intervention. MAIN RESULTS: Of those enrolled, 100 provided consent for family involvement. Seventy-three of the 100 were sent a mailer to engage them in care; none became involved. Clinicians were provided assessment data on their patients and notified of 50 patients needing family services. Of those 50, 6 families were already involved, 34 were never contacted, and 10 were contacted; 7 new families became involved in care. No families were referred to the family psychoeducational program. CONCLUSIONS: Uptake of the family intervention failed due to barriers from all stakeholders. Families did not respond to the mailer, patients were concerned about privacy and burdening family, clinicians had misperceptions of family-patient contact, and organizations did not free up time or offer incentives to provide the service. If a full partnership with patients and families is to be achieved, these barriers will need to be addressed, and a family-friendly environment will need to be supported by clinicians and their organizations. Applicability to family involvement in other disorders is discussed.